Composite of perovskite and fluorite fuel electrodes for efficient carbon dioxide electrolysis in solid oxide electrolyzer cells - Li, Hao-Yang (2024)
Solid oxide electrolyzer cells (SOECs) convert greenhouse gases electrochemically to useful forms of fuels, where the key to efficient conversion lies in the selection of fuel electrodes for CO2 reduction. Mixed ionic and electronic conducting (MIEC) perovskites composited with fluorites are state-of-the-art fuel electrodes with increased surface reaction sites and bulk diffusion rates. We demonstrate the composite fuel electrode Sr2Fe1.5Mo0.5O6−δ (SFM)-Ce0.6Mn0.3Fe0.1O2−δ (CMF) for good CO2 reduction in SOECs. The composite of SFM MIEC perovskite with the CMF fluorite, which is a good ionic conductor, has significantly improved the electro-catalytic activity not only due to the better electro-catalytic activity in CMF than SDC but also due to the stronger mutually electronic activation effect between CMF and SFM perovskite oxide. The SOECs using the SFM-CMF composite fuel electrode for CO2 reduction showed excellent electrochemical performance of 3.02 A cm−2 at 1.6 V and 1073 K without further engineering in the perovskite phase.